Serological signature of tick-borne pathogens in Scandinavian brown bears over two decades - Paillard, Lye; Jones, Krista; Evans, Alina; Berret, Jérémy; Jacquet, Maxime; Lienhard, Reto; Bouzelboudjen, Mahmoud; Arnemo, Jon; Swenson, Jon; Voordouw, Maarten (BioMed Central Ltd., 2015)
Abstract Background Anthropogenic disturbances are changing the geographic distribution of ticks and tick-borne diseases. Over the last few decades, the tick Ixodes ricinus has expanded its range and abundance considerably in northern Europe. Concurrently, the incidence of tick-borne diseases, such as Lyme borreliosis and tick-borne encephalitis, has increased in the human populations of the Scandinavian countries. Methods Wildlife populations can serve as sentinels for changes in the distribution of tick-borne diseases. We used serum samples from a long-term study on the Scandinavian brown bear, Ursus arctos , and standard immunological methods to test whether exposure to Borrelia burgdorferi sensu lato, the causative agent of Lyme borreliosis, and tick-borne encephalitis virus (TBEV) had increased over time. Bears had been sampled over a period of 18 years (1995–2012) from a southern area, where Ixodes ricinus ticks are present, and a northern area where ticks are uncommon or absent. Results Bears had high levels of IgG antibodies against B. burgdorferi sensu lato but not TBEV. Bears at the southern area had higher values of anti- Borrelia IgG antibodies than bears at the northern area. Over the duration of the study, the value of anti- Borrelia IgG antibodies increased in the southern area but not the northern area. Anti- Borrelia IgG antibodies increased with the age of the bear but declined in the oldest age classes. Conclusions Our study is consistent with the view that ticks and tick-borne pathogens are expanding their abundance and prevalence in Scandinavia. Long-term serological monitoring of large mammals can provide insight into how anthropogenic disturbances are changing the distribution of ticks and tick-borne diseases.